Integrating Financial Literacy, Financial Technology, and MSME Performance with Moderated Networking to Support Sustainable Production Methods - Muhammad Arry Wahyudi; Shwu-Jen Lin (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to analyze the influence of financial literacy and financial technology on the performance and sustainability of MSMEs, with performance as a mediating variable and networking as a moderating variable. Methodology: The research method used was explanatory research with a quantitative approach. Data were obtained from 80 food and beverage MSMEs in Genuk District, Semarang, using a Likert-scale questionnaire and analyzed using multiple linear regression, the Sobel test, and Moderated Regression Analysis (MRA). Main Findings: The research results show that financial literacy and financial technology have a positive and significant impact on the performance and sustainability of MSMEs. MSME performance has also been shown to improve business sustainability. However, networking does not strengthen the relationship between financial literacy and performance; instead, it only enhances the influence of financial technology on MSME performance. Novelty/Originality of this study: This finding provides a theoretical contribution by emphasizing that the sustainability of MSMEs is not only determined by financial literacy and the use of fintech, but also by the synergy between business performance and the social networks owned by MSME actors.